Managing teams - Holpp, Lawrence (New York McGraw-Hill, 1999)
Managing Teams will dramatically increase your chances for a smooth transition to a highly productive team. This handy guide includes methods and checklists to determine how to assemble the best team, tips on improvements you should expect - and not expect - from teams, and strategies for recognizing and avoiding major roadblocks in creating a team environment. Managing Teams will provide the support and confidence you need to initiate and manage workplace teams, evaluate the success of those teams, and get your employees working in a coordinated, disciplined manner
Questions to ask before starting teams -- Creating the culture for teamwork -- Teams and business strategy -- Why organizations have problems with teams -- Vision, values, mission, and strategy -- Team dynamics -- New roles for leaders of high-performance work groups -- Conducting team meetings -- Coaching teams and team members -- Coping with conflicts and changes -- Applied empowerment -- Evaluating your team
Includes index
Keywords: Teams in the workplace -- Management